S47 Neural respiratory drive responses to increases in continuous positive airway pressure in healthy subjects. (12th November 2015) - Suh, ES; Mandal, S; Ramsay, MC; Rafferty, G; Moxham, J; Hart, N
Abstract : Introduction: Dynamic hyperinflation (DH) is characterised by an increase in end-expiratory lung volume (EELV) and contributes to exercise limitation in Chronic Obstructive Pulmonary Disease (COPD) patients. Neural respiratory drive (NRD) directly reflects the load-capacity relationship of the respiratory system and is therefore expected to increase with DH. However, there are limited data investigating the effects of isolated increases in EELV on NRD. We hypothesised that 1) increases in EELV induced by continuous positive airway pressure (CPAP) would increase NRD in healthy subjects and 2) with the change in lung volume, NRD to the parasternal intercostal muscles would increase to a greater extent than that to the diaphragm at higher levels of CPAP. Method: CPAP was applied to healthy subjects at 0, 4, 8, 12 and 16 cmH2 O in a random order and inspiratory capacity (IC) measured at each CPAP level as an indicator of EELV. Transdiaphragmatic pressure swings (ΔPdi ), tidal volume (VT ) and respiratory rate (RR) were measured. NRD was assessed with second intercostal space parasternal muscle electromyography (EMGpara ) and diaphragm electromyography (EMGdi ) using surface electrodes and a multipair oesophageal electrodes, respectively. EMGpara /EMGdi ratio was calculated. Results: 10 healthy subjects were recruited. Increasing levels of CPAP led to a reduction in IC (p < 0.0001, Table 1 ). Both EMGpara and EMGdi increased with progressive increases in CPAP (Table 1). Interestingly, respiratory rate and tidal volume did not change with the increases in CPAP. Similarly, EMGpara /EMGdi ratio and ΔPdi remained unchanged. Conclusion: This detailed physiological study has demonstrated that escalating levels of CPAP increased EELV, shown by the reduction in IC, in healthy subjects. The increase in EELV was associated with an increase in NRD to both the parasternal intercostal muscles and to the diaphragm. However, contrary to the original hypothesis and observations in COPD patients (O'Donoghue et al ., Thorax 2001), NRD was not preferentially distributed to the parasternal intercostal muscles at higher lung volumes. These data indicate that the differential NRD to the parasternal and diaphragm in COPD patients is not solely a consequence of a rise in EELV and alternative mechanisms for the differential NRD should be sought. Reference: 1 O'Donoghue FJ, Catcheside PG, Jordan AS, et al. Effect of CPAP on intrinsic PEEP, inspiratory effort, and lung volume in severe stable COPD. Thorax . 2002;57 :533–9